(untitled) (Bangladesh Journal of Medical Biochemistry, 2013)
Glomerular filtration rate (GFR) is the best single measure of overall function of kidney. GFR is routinely assessed by measuring the concentration of endogenous serum markers such as blood urea nitrogen and serum creatinine (SCr). Although widely used these endogenous marker are not ideal and do not perform optimally in certain clinical settings. The purpose of this review is to critically review the potential utility of Cys C as a new promosing markers of GFR and to review whether Cys C had any advantage over routinely used endogenous marker in different population group. DOI: http://dx.doi.org/10.3329/bjmb.v6i1.13284 Bangladesh J Med Biochem 2013; 6(1): 26-30